A Lower HCC Incidence in Chronic HBV-Infected Patients Recovered from Acute-on-Chronic Liver Failure: A Prospective Cohort Study. (27th October 2022) - Yin, Jianhua; Xu, Xiang; Pu, Rui; Su, Haibin; Wang, Junxue; Liu, Wenbin; Tong, Jingjing; Chen, Jing; Chen, Xi; Mu, Xiuying; Zhang, Hongwei; Zhai, Xingran; et al.
Abstract : Background . Activation of chronic hepatitis B virus (HBV) infection is an important cause of acute-on-chronic liver failure (ACLF). However, the effect of HBV-ACLF episode on hepatocellular carcinoma (HCC) occurrence remains largely unknown. Methods . A total of 769 HBV-ACLF patients and 2114 HBV-related chronic liver disease (HBV-CLD) patients diagnosed between August 1998 and December 2011 were enrolled in this prospective cohort study. Of the HBV-CLD patients, 380 received lifetime antiviral treatment with nucleos(t)ide analogues. Propensity score matching was applied to reduce baseline differences between HBV-ACLF and HBV-CLD cohorts. Results . The survival rate of HBV-ACLF patients was 53.6%, 50.3%, 47.8%, and 46.2% at 90-day, 1-year, 5-year, and 10-year, respectively. The cumulative incidence of HCC was lower in HBV-ACLF cohort with 369 eligible patients survived for >90 days than in HBV-CLD cohort with the 380 patients (5.77/1, 000 vs. 9.78/1, 000 person-years, p = 0.0497 ). HBV-ACLF episode decreased HCC risk regardless of liver cirrhosis, and in patients without family history of HCC. Multivariate Cox analyses indicated that male, increasing age, liver cirrhosis, and platelet count (≤100 × 10 9 /L) increased, whereas HBV-ACLF episode decreased, HCC risk independently. In the propensity score-matched cohorts, HBV-ACLF episode reduced HCC incidence (10.20/1, 000 vs. 4.66/1, 000 person-years, p = 0.0326 ). The area under curve of nomogram was 0.812 for 3-year HCC probability. Conclusions . HBV-ACLF episode decreases HCC occurrence in chronic HBV patients. Older age and liver cirrhosis independently increased HCC occurrence. A nomogram-enrolled episode of ACLF reliably predicts the occurrence of HCC.